2006
DOI: 10.1007/s10529-005-5132-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of a β-1,3-glucanase from Chaetomium sp. that is Involved in Mycoparasitism

Abstract: A beta-1,3-glucanase was detected, using laminarin as substrate, in the culture broth of Chaetomium sp. Major activity was associated with a 70 kDa protein band visualized on a polyacrylamide gel. beta-1,3-Glucanase was purified by a one-step, native gel purification procedure. Optimal activity was observed at pH 6.0 and 30 degrees C (over 30 min). It could degrade cell walls of plant pathogens including Rhizoctonia solani, Gibberella zeae, Fusarium sp., Colletotrichum gloeosporioides and Phoma sp. The N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Trichoderma koningii inhibits the growth of Sclerotium cepivorum in onion root via the production of exo- and endo-chitinases, which digest the cell walls of pathogens [42]. β-1, 3-glucanase, also associated with mycoparasitism, induces strong hydrolysis of pathogen cell walls, thereby inhibiting germination of pathogen spores and digestion of the mycelium [43]. In addition, proteases play an important role in mycoparasitism, as they are necessary for the complete hydrolysis of pathogen cell walls [44].…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma koningii inhibits the growth of Sclerotium cepivorum in onion root via the production of exo- and endo-chitinases, which digest the cell walls of pathogens [42]. β-1, 3-glucanase, also associated with mycoparasitism, induces strong hydrolysis of pathogen cell walls, thereby inhibiting germination of pathogen spores and digestion of the mycelium [43]. In addition, proteases play an important role in mycoparasitism, as they are necessary for the complete hydrolysis of pathogen cell walls [44].…”
Section: Discussionmentioning
confidence: 99%
“…NoS3 from Nerium oleander L. with strong antioxidant activity. Sun et al (2006) reported the antifungal activity of Chaetomium sp. and isolated from it an extracellular b-1, 3-glucanase.…”
Section: Identification Of 48 Strains Belonging To Sordariomycetesmentioning
confidence: 99%
“…and R. solani, P. byssoides and plant pathogenic fungi were inoculated on the surface of a water agar (2% w/v) plate (9 cm), and they were incubated on opposite each other (6 cm) (Sun et al 2006). The interactions between P. byssoides and the plant pathogenic fungi were examined under a light microscope after culturing for 3-15 days at 27°C.…”
Section: Dual-culture Plate Assaymentioning
confidence: 99%